Evaluating clinical outcomes associated with ectopic pregnancies - Banotra, Palvi; Rashid, Adil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Ectopic pregnancy refers to the implantation of a fertilized ovum outside the endometrium. There is no doubt that ectopic pregnancy is a common cause of morbidity; however, the associated mortality has declined significantly over the years due to early diagnosis and timely intervention. Methods: This prospective study was conducted at Lala Ded Hospital, Srinagar from April 2016-March 2017. All the patients with ectopic pregnancies admitted through accident and emergency unit and through gynaecoloy out-patient department were included in the study. The data on several factors was analyzed like; parity, clinical presentation, risk factors, management and findings at laparotomy, to draw a valid inference. All the patients were managed as per hospital protocol and followed till discharge from the hospital. Results: The present study revealed that the commonest age group affected with ectopic pregnancies is 20-24 years with majority of patients having previous spontaneous abortion as being high risk factor associated with ectopic pregnancies followed by pelvic inflammatory disease. The most dominant clinical presentation among the study subjects was pain and the commonest site of ectopic pregnancy was ampulla region of fallopian tube. Most of the patients were successfully managed with the help of salpingectomy Conclusions: We suggest that the possibility of ectopic pregnancies should not be ignored in the reproductive age group especially in patients presenting with severe abdominal pain because delayed diagnosis often halts timely intervention which in turn invite serious health consequences.